Degradation of red 5B and reactive blue 5G dyes in synthetic textile dye effluent by photo-fenton process - Finger, Leandro; Quitaiski, Poliana Paula; Mees, Juliana Bortoli Rodrigues; Costa Junior, Ismael Laurindo (Eclética Química, 2018)
Effluents from textile industries are difficult to treat because they are loaded with non-biodegradable dyes. In this context, the Advanced Oxidation Processes (AOPs) are presented as alternatives to be studied for the treatment of these effluents. The objective of this work was to evaluate the efficiency of the removal of red 4B and 5G blue dyes in synthetic solution by means of the advanced oxidation Photo-Fenton. The best pH for removal of Red 4B was pH 3 and for Blue 5G dye was pH 1.6. The obtained results report a good removal when using H2O2 and Fe2+. With a H2O2 concentration of 66.80 mg L-1, Fe2+ of 9.66 mg.L-1 and pH 5.81 with a predicted percentage removal of 100.01% for Red 4B dye. And for Blue Reactive 5G dye a concentration of H2O2 of 55,04 mg L-1, Fe2+ of 10.34 mg L-1 and pH 2.59 with an expected percentage removal of 100,56%. The kinetics was that pseudo-first order with k1 of 0,597 min-1 and t1/2 of 1,16 min for red 4B and k1 of 0,150 min-1 and t1/2 of 4,60 for blue 5G. The results indicate the application of photo-fenton as promising for the dyes removal in aqueous solutions.